(untitled) (Journal of Organizational Psychology, 2020)
Job insecurity is a crucial employee attitude to study, especially in challenging economic times. The current study uses a multilevel modeling approach to evaluate the predictors of job insecurity, both at the employee-level (Nemployees=1144) and organizational division-level (Ndivisions=25) among university staff and faculty at a university in the southern United States. The results indicate that employee-level justice perceptions, constraints, and pay and communication satisfaction influence job insecurity as well as division-level perceived supervisor support. Overall, this study helps identify mechanisms that are largely in the organization’s control which could lessen feelings of job insecurity among its employees.